2014
DOI: 10.3233/thc-130765
|View full text |Cite
|
Sign up to set email alerts
|

Navigated reconstruction of tibial head depression fractures by inflation osteoplasty

Abstract: BACKGROUND: Articular fracture reduction control remains a challenge even with the development of computer-assisted surgery. The Kyphoplasty procedure has shown advantages in treating vertebral fractures. One case report showed successful reduction of acetabular fractures using Kyphoplasty. OBJECTIVE: This study examines the efficacy of this method in reducing depressed tibial plateau fractures. METHODS: An insertion sleeve for the Kyphon balloon that could be calibrated by the navigation system was designed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In recent literature, two experimental–biomechanical 8,9 and few cadaveric and clinical studies 10 –12 have shown good results for the short term in five patients. Furthermore, calcium phosphate cement augmentation has better mechanical stability than the use of cancellous bone.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In recent literature, two experimental–biomechanical 8,9 and few cadaveric and clinical studies 10 –12 have shown good results for the short term in five patients. Furthermore, calcium phosphate cement augmentation has better mechanical stability than the use of cancellous bone.…”
Section: Introductionmentioning
confidence: 94%
“…Indication for balloon repositioning and tibioplasty includes depression fractures and combined depression fractures in the medial or lateral tibial plateau area. [5][6][7] In recent literature, two experimental-biomechanical 8,9 and few cadaveric and clinical studies [10][11][12] have shown good results for the short term in five patients. Furthermore, calcium phosphate cement augmentation has better mechanical stability than the use of cancellous bone.…”
Section: Introductionmentioning
confidence: 99%